(untitled) (Jurnal Pembangunan Sosial, 2011)
Development generally produced certain impacts on older people. Despite development creates a lot of employment opportunities, these opportunities only suitable for younger generation. The elderly in general are becoming more marginalized and still continue their traditional activities. This paper aims at discussing the economic activities of the elderly in the tourism development in Pulau Perhentian, Terengganu. Results indicated that economic activity of the elderly is still on fishing activities, and many other traditional occupations, such as selling vegetable crops and managing food stalls.